2020
DOI: 10.1097/mpg.0000000000002761
|View full text |Cite
|
Sign up to set email alerts
|

Low Splanchnic Oxygenation and Risk for Necrotizing Enterocolitis in Extremely Preterm Newborns

Abstract: Objective: The aim of the study was to investigate whether splanchnic oxygenation (SrSO2), measured with near-infrared spectroscopy (NIRS), during the first week of life is associated with the risk of developing necrotizing enterocolitis (NEC) in extremely preterm infants. Methods: This was a prospective observational cohort study including extremely preterm infants (<28 weeks of gestation) born at Karolinska University Hospital from September 2014 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Infants with necrotizing enterocolitis (Bell's stage ≥2) 18 were also excluded because of the association of r s SO 2 in the first week after birth and subsequent development of necrotizing enterocolitis. 7,19 Data from infants who developed clinical sepsis (sepsis symptoms with a positive blood culture and/or C-reactive protein >20 mg/L) were excluded from 1 day prior to diagnosis and all subsequent days because intestinal perfusion has been shown to be different during these days in these infants. 20 In case an infant died, data from that day were excluded.…”
Section: Patient Populationmentioning
confidence: 99%
“…Infants with necrotizing enterocolitis (Bell's stage ≥2) 18 were also excluded because of the association of r s SO 2 in the first week after birth and subsequent development of necrotizing enterocolitis. 7,19 Data from infants who developed clinical sepsis (sepsis symptoms with a positive blood culture and/or C-reactive protein >20 mg/L) were excluded from 1 day prior to diagnosis and all subsequent days because intestinal perfusion has been shown to be different during these days in these infants. 20 In case an infant died, data from that day were excluded.…”
Section: Patient Populationmentioning
confidence: 99%
“…The earlier the birth, the higher the incidence, which is not related to whether surgical intervention occurred. The pathogenesis of NEC has not been fully clarified yet, but it has been reported to be related to immune disorders, acute inflammatory cascade reactions, and mucosal barrier function damage ( 20 ). This study found that the concentrations of CRP, I-FABP, IL-6, PCT, and SAA in the operation group were notably higher, indicating that the inflammatory reaction and intestinal mucosa damage in NEC patients were more serious.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral and splanchnic oxygenation monitoring was performed at postnatal age between days 2 and 6, within 96 h after the first enteral feeding. This population has been described in detail in a previous publication [ 8 ]. A near infrared spectroscopy (NIRS) INVOS 5100c monitor (Medtronic™, (Minneapolis,) USA) with neonatal INVOS sensors was used to measure cerebral (CrSO 2 ) and splanchnic regional oxygenation (SrSO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, demographic and clinical variables were compared between the two cohorts. Second, we divided all infants based on the SrSO 2 30% cut off [ 8 ]. Third, specificity, sensitivity, and positive and negative predictive values with confidence intervals were calculated with a bootstrap cross-validation in R 4.1.2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation